Pengaruh Pemberian Sari Wortel (Daucus carota L.) terhadap Tukak Lambung Pada Tikus Putih Jantan - Suhatri Suhatri; Rusdi Rusdi; Emi Sugesti (Fakultas Farmasi Universitas Andalas, 2015)
A study on the effect of carrot decoction to the gastric ulcer of white male rats induced by absolute ethanol 1 ml/200 g orally has been conducted. The study showed that carrot decoction in the doses of 3; 6; and 12 ml/kg could improve the ulcer by amount of 28.41; 46.79; and 75.76 %, respectively. The decoction could also reduce the pH of gastric juice significantly toward the normal level (P<0.01).